Analysis on the Crystal Structure of the Piezoelectric Nanocrystal Ceramic of Pr-doped Bi1/2Na1/2TiO3 using Molten-Salt Synthesis - Ahda, Syahfandi; Ambarwati, Vita; Mardiyanto, Mardiyanto; Sukirman, Engkir; Sugeng, Bambang (Makara Journal of Science, 2021)
One of the future technologies in nuclear reactors is the ability of piezoelectric materials to monitor reactor cores as sensors. Particularly, Pb-free piezoelectric materials, such as Bi1/2Na1/2TiO3, have been examined to improve the ability of their piezoelectric properties. In this study, we attempted to add Pr6O11 dopant material with mole ratios of 0, 0.3, 0.5, and 0.7 mol%. The synthesis process used in this study is the molten-salt synthesis method with a NaCl and KCl salt mole ratio of 1:1. The crystal structure analysis using the refinement process of the Rietveld method of the HighScore software was performed. Accordingly, a rhombohedral crystal structure system with lattice parameters of 3.8809(2), 3.8831(2), 3.8834(7), and 3.8816(2) angstroms and variations in the content of Pr6O11 was obtained. The optimal lattice parameter was discovered with the addition of 0.5 mol% of Pr6O11. The morphology of the synthesis product is still unclear for each addition of dopant material due to the large number of granular agglomerations.